2009
DOI: 10.1016/j.jbankfin.2009.02.002
|View full text |Cite
|
Sign up to set email alerts
|

The wandering weekday effect in major stock markets

Abstract: JEL classification: G14 G15Keywords: Seasonality Weekday effect Monday effect Market efficiency Stock markets a b s t r a c t This paper reports a wandering weekday effect: the pattern of day seasonality in stock market returns is not fixed, as assumed in the Monday or weekend effects, but changes over time. Analysing daily closing prices in eleven major stock markets during 1993-2007, our results show that the wandering weekday is not conditional on average returns in the previous week (the ''twist" in the Mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(58 citation statements)
references
References 30 publications
2
53
1
2
Order By: Relevance
“…Research studies have documented many anomalous evidences regarding the stock market ef iciency such as January effect (Seyhun, 1993), day of the week effect (Wingender and Groff, 1989), Monday effect (Cho et al, 2007;Jaffe and Wester ield, 1985b), and wandering weekend effect (Doyle and Chen, 2009). Recently, studies have found the irrational behaviour of security prices during the Islamic calendar months such as Ramadan effect (Białkowski et al, 2012).…”
Section: Background Of the Studymentioning
confidence: 99%
“…Research studies have documented many anomalous evidences regarding the stock market ef iciency such as January effect (Seyhun, 1993), day of the week effect (Wingender and Groff, 1989), Monday effect (Cho et al, 2007;Jaffe and Wester ield, 1985b), and wandering weekend effect (Doyle and Chen, 2009). Recently, studies have found the irrational behaviour of security prices during the Islamic calendar months such as Ramadan effect (Białkowski et al, 2012).…”
Section: Background Of the Studymentioning
confidence: 99%
“…I follow Doyle and Chen (2009) to address the fixed-effect assumption by separating the full sample into one-year sub-samples, estimating the model for each sub-sample, and examining the way in which the effects change annually over the course of the full sample. The one-year sub-samples should be short enough to accommodate possible changes for the effects.…”
Section: Fixed-effect Assumptionsmentioning
confidence: 99%
“…In their study, Doyle and Chen (2009) also proposed a comprehensive model in which the full-sample data were considered and in which individual coefficients were assigned to measure the effects of the one-year sub-samples. The comprehensive model allowed the researchers to test for significant weather effects jointly using Wald tests or F-tests; however, I do not adopt the comprehensive model.…”
Section: Fixed-effect Assumptionsmentioning
confidence: 99%
See 1 more Smart Citation
“…4 Bailey et al [1] propose a method to determine the degree to which a particular backtest may have been compromised by the risk of overfitting. …”
Section: Global Constraintmentioning
confidence: 99%